Treatment-relevant biomarkers in gynecologic oncology - Ditsch, Nina; Fasching, Peter (Die Gynäkologie, 2022)
The first biomarkers were discovered decades ago. Their prognostic and predictive value is still the subject of current research. Biomarker-based treatments represent the basis of the current and future trial landscape in gynecologic oncology, as was clearly demonstrated at this year's ASCO Annual Meeting. The all-important question is founded in the quality of diagnostics at the immunohistochemical or molecular level. In breast cancer therapy, a HER-2 (human epidermal growth factor receptor 2) finding was previously considered therapeutically relevant if there was an immunohistochemical (IHC) evaluation of 3+ or a fluorescence in situ hybridization (FISH)- or chromogenic in situ hybridization (CISH)-positive value. Use of the antibody-drug conjugate trastuzumab-deruxtecan, also in HER-2-low forms (IHC1+ or 2+, even if FISH/CISH negative), is now celebrated as practice changing, since significantly improved progression-free survival (PFS) and overall survival (OS) were also shown in this situation. With the accelerating use of newer therapeutics, attention should be paid to the side effects and the cost-benefit ratio. The following article provides an overview of the currently most important prognostic and predictive markers in breast, ovarian, endometrial, and cervical cancer.
CRIS-Team WoS Importer:2022-09-09